2010
DOI: 10.1016/j.epsl.2009.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of lateral sediment transport in the Panama Basin as revealed by radiocarbon ages of alkenones, total organic carbon and foraminifera

Abstract: Paired radiocarbon measurements on haptophyte biomarkers (alkenones) and on cooccurring tests of planktic foraminifera (Neogloboquadrina dutertrei and Globogerinoides sacculifer) from late glacial to Holocene sediments at core locations ME0005-24JC, Y69-71P, and MC16 from the south-western and central Panama Basin indicate no significant addition of pre-aged alkenones by lateral advection. The strong temporal correspondence between alkenones, foraminifera and total organic carbon (TOC) also implies negligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 78 publications
0
24
0
2
Order By: Relevance
“…Kusch et al . [] have measured radiocarbon ages on paired fine‐grained (alkenone) and coarse‐grained (foraminifera) samples which do not show evidence for addition of older fine‐grained material.…”
Section: Discussionmentioning
confidence: 99%
“…Kusch et al . [] have measured radiocarbon ages on paired fine‐grained (alkenone) and coarse‐grained (foraminifera) samples which do not show evidence for addition of older fine‐grained material.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sea level fluctuations and shore line positions during MIS3 would not be conducive for remobilization of sediments on the continental shelves. Local contemporaneous redistribution of sedimentary constituents has occurred in the Panama Basin, as shown by insignificant radiocarbon age differences between organic carbon, planktonic foraminifera and alkenones in cores ME‐24 and closely adjacent Y69‐71P [ Kusch et al , 2010], demonstrating that the material that has inflated the bulk sediment accumulation rate over that supplied from the sea surface has not been preaged but has been moved syndepositionally to the core sites. This strongly implies that the downcore proxy record in this region of the EEP is a faithful record of paleoceanographic and sedimentary events despite clear evidence of sediment focusing [ Kienast et al , 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the concentration of opal in the deep basins (and of calcite on the ridges) in the EEP is more closely related to topography than to productivity [ Moore et al , 1973]. Kusch et al [2010] have shown that the focusing of sediment at some core sites in the EEP is due to the syndepositional accumulation of material that has not been significantly aged, indicating that short‐distance bottom redistribution of material has inflated the sediment record but has not seriously biased it.…”
Section: Silica Supply and Opal Burial In The Eepmentioning
confidence: 99%
“…The degree of spatial averaging can vary across different settings depending on catchment size, basinal morphology and biomarker transport pathways . Additionally, it has been shown that biomarkers can have a long residence time in soils on the order of centuries or longer (Drenzek et al, 2009;Kusch et al, 2010;Douglas et al, 2014). Therefore, long chain leaf wax n-alkanes preserved in sedimentary archives are most likely a mixture of aquatic plants, fresh vascular plant debris, and older soil and/or sedimentary organic matter.…”
Section: Introductionmentioning
confidence: 99%